2022
DOI: 10.3390/cancers14184400
|View full text |Cite
|
Sign up to set email alerts
|

Cachexia Index as a Prognostic Indicator in Patients with Gastric Cancer: A Retrospective Study

Abstract: The current diagnostic criteria for cancer cachexia are inconsistent, and the prognostic value of cachexia in gastric cancer (GC) is controversial. This study aimed to investigate the prognostic value of the cachexia index (CXI) in patients with GC. We calculated the CXI as skeletal muscle index (SMI) × serum albumin/neutrophil-lymphocyte ratio (NLR), and a total of 161 and 163 patients were included in the high and low CXI groups, respectively. Low CXI was significantly associated with a more advanced tumor–n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
(47 reference statements)
2
8
1
Order By: Relevance
“…The discrepancy between Cang et al [17] and our results is that in their subgroup analyses, they reported that CXI was associated with OS regardless of age, while we showed that CXI was associated with OS only in elderly and not in non-elderly patients (Electronic Supplementary Information; online suppl. Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The discrepancy between Cang et al [17] and our results is that in their subgroup analyses, they reported that CXI was associated with OS regardless of age, while we showed that CXI was associated with OS only in elderly and not in non-elderly patients (Electronic Supplementary Information; online suppl. Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we showed that CXI was predictive of OS rates in patients with GC undergoing gastrectomy, independent of cancer staging. Our results agreed with Cang et al [17]. Our study is the first to elucidate the impact of CXI in GC CSS and show that CXI is a prognostic factor for CSS in GC patients undergoing gastrectomy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several studies have demonstrated the potential efficacy of CXI as a biomarker to predict cancer patients' prognosis. 4,5 However, the practical application of CXI is limited by the associated cost and complexity of skeletal muscle index testing procedures. Sadly, recent research on developing CXI has been at a standstill.…”
mentioning
confidence: 99%
“…Mechanical obstruction of the pyloric duct due to tumor progression causes patients to suffer from digestive system symptoms such as abdominal pain, bloating and loss of appetite, which severely affects energy intake. The increase in energy consumption caused by cancer makes the nutritional status of patients with pyloric stenosis deteriorate rapidly, even leading to cachexia (7)(8)(9). Numerous studies have explored that poor nutritional status was an important negative influence on the development of postoperative complications and on prognosis (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%